2003
DOI: 10.1103/physrevb.68.024403
|View full text |Cite
|
Sign up to set email alerts
|

Spin polarization of magnetoresistive materials by point contact spectroscopy

Abstract: In the strive to find a straightforward method for determining the spin polarization, the analysis of the Andreev reflection process in point contact junctions has attracted much interest. However, the prerequisite for an evaluation of the transport spin polarization in this scheme is the existence of elastic (ballistic or diffusive) transport, which cannot be assumed a priori. We therefore also include inelastic processes in our analysis and exemplify that thermal effects can have a significant effect on data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
51
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 21 publications
2
51
1
Order By: Relevance
“…Very recently, Marukame et al [31] reported a TMR ratio of 74% at 55K for a Co 2 Cr 0.6 Fe 0.4 Al-MgO-CoFe magnetic tunnel junction. A spin polarisation of only less than 49% was found for polycrystalline samples by means of Andreev reflections [32]. The observation of an incomplete spin polarisation may not only be caused by the model used to interpret the data [32,33] but also by the properties of the sample.…”
Section: Introductionmentioning
confidence: 98%
“…Very recently, Marukame et al [31] reported a TMR ratio of 74% at 55K for a Co 2 Cr 0.6 Fe 0.4 Al-MgO-CoFe magnetic tunnel junction. A spin polarisation of only less than 49% was found for polycrystalline samples by means of Andreev reflections [32]. The observation of an incomplete spin polarisation may not only be caused by the model used to interpret the data [32,33] but also by the properties of the sample.…”
Section: Introductionmentioning
confidence: 98%
“…Conversely, at a fixed exchange energy, an increase in Fermi velocity mismatch could increase the subgap conductance. 100 In a typical interpretation of a measured conductance, complications can then arise in trying to disentangle the influence of parameters Z, P G , and Fermi velocity mismatch from the nature of the point contacts (Kikuchi et al, 2002) and the role of inelastic scattering (Auth et al, 2003). Detection of P in a high-temperature superconductor is even possible with a large barrier or a vacuum between the F and S regions, as proposed by Wang and Hu (2002) using resonant Andreev reflection and a d-wave superconductor.…”
mentioning
confidence: 99%
“…Cobalt-based full-Heusler alloys have been considered potential candidates for showing HMF properties. Their structural and magnetic properties have been intensively investigated experimentally [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and theoretically [19][20][21][22][23] because they have comparatively high Curie temperatures T C . In particular, Co 2 Cr 1−x Fe x Al (CCFA) is expected to have suitable electro-magnetic properties for injecting a spinpolarized current [16,22].…”
Section: Introductionmentioning
confidence: 99%